Streptocyclinones A and B ameliorate Alzheimer's disease pathological processes in vitro. (October 2018) - Alvariño, Rebeca; Alonso, Eva; Lacret, Rodney; Oves-Costales, Daniel; Genilloud, Olga; Reyes, Fernando; Alfonso, Amparo; Botana, Luis M.
Abstract: Alzheimer's disease (AD) is a pathology characterized by the abnormal accumulation of amyloid-beta (Aβ) and hyperphosphorylated tau. Oxidative stress and neuroinflammation are also strongly related to this disease. The ability of two new glycosylated angucyclinones, streptocyclinones A and B (1 and2 ), isolated from Streptomyces sp to improve AD hallmarks was evaluated. Compounds were able to protect SH-SY5Y neuroblastoma cells from H2 O2 -induced oxidative injury by activating the nuclear factor E2-related factor (Nrf2). Their capacity to modulate neuroinflammation was tested in lipopolysaccharide-activated BV2 microglial cells. Compounds reduced the release of pro-inflammatory factors, inhibited the activation of NFκB and mitogen activated kinases (MAPK), and induced the translocation of Nrf2 to the nucleus of microglial cells. A trans-well co-culture was established to determine the effect of microglia treated with streptocyclinones on the survival of SH-SY5Y cells. The cell viability of neuroblastoma cells increased when the compounds were added to BV2 cells. SH-SY5Y-TMHT441 cells were used to determine the effect of compounds on tau phosphorylation. Both compounds reduced tau hyperphophorylation by targeting MAPK kinases. Moreover, streptocyclinone B (2 ) was able to inhibit the activity of β-secretase 1 and decrease the release of reactive oxygen species in BV2 cells stimulated with Aβ. With the same co-culture trans-well system, the treatment of Aβ-stimulated microglia with compound2 augmented the viability of SH-SY5Y-TMHT441 cells. The results presented in this work provide evidences of the multitarget activities displayed by these new Streptomyces compounds, making them good candidates for further studies in the treatment of AD. Graphical abstract: Highlights: Streptocyclinones protect SH-SY5Y cells from oxidative stress by activating Nrf2. Compounds modulate neuroinflammation by NFκB and MAPKs inhibition and Nrf2 activation. Tau hyperphosphorylation is reduced by compounds through inhibition of MAPK kinases. Streptocyclinone B inhibits BACE1 and decreases ROS release in Aβ-activated BV2 cells. Neuronal cells are protected by compounds in trans-well co-cultures with microglia.